A METHOD TO DEFINE THE SPATIAL STATIONS LOCATION IN A CARSHARING SYSTEM IN SÃO PAULO – BRAZIL - M. O. Lage; C. A. S. Machado; F. Berssaneti; J. A. Quintanilha (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
Sharing mobility systems have become part of a sociodemographic trend that has pushed shared modes from the fringe to the mainstream of the transportation systems. Carsharing is a mode of shared transport, where a service is offered in which several people share the access and use of a set of vehicles. This is a relatively new mode of urban transport, which gives users access for short periods of rental, thus providing the benefits of using private vehicles, while avoiding the inherent property charges of a vehicle. The objective of the article searches for the identification and selection of preferred areas in the São Paulo City (Brazil) to implement a prototype of a carsharing system. The adopted methodology of demand analysis identifies the spatial patterns of the intervening variables of socioeconomic information, transportation and land use, in order to understand the current panorama of the demand for transport in São Paulo. The analysis made it possible to identify and select preferred areas in São Paulo for the implementation of a prototype. The study indicated the most favorable places to receive the service stations to operate a carsharing system.